GAMBARAN RUMAH SAKIT UMUM DAERAH KABUPATEN BATANG DALAM PENERAPAN GREEN HOSPITAL DI KABUPATEN BATANG - Rahmi Nur Alifiani; Mursid Rahardjo; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2018)
Batang District Hospital is a type C hospital that haven’t entirely applied environmental friendly hospital building concept that empowering the power of nature as a main resource with the result as feared in environmental management could pollute the environment. The purpose of this study is to review the quality of environmental in RSUD Kabupaten Batang toward the implementation of green hospital. This study is qualitative study with descriptive approach. Sampling for this study using purposive technique sampling consist of 8 main informants and 1 triangulation informant. Result for 10 assessment aspects show that leadership aspect had achieved 2 points, location and landscape had achieved 3 points, hospital building had achieved 2 points, energy efficiency had achieved 1 point, water conservation had achieved 2 points, hospital waste had achieved 4 points, chemical material had 0 poin, environmental hygiene and vector control had achieved 3 points, food processing had achieved 2 points, and air quality had achieved 2 points. Based on data that have been collected and point counting refers to Green Building Council Indonesia, WHO guidance, hospital PROPER assessment, Goverment Regulation of Public Works No. 02 year 2015, and Health Minister Decision No. 1204 year 2004 with percentage as much as 48,84% that had fulfilled standard score 21 points from maximal 43 points. Batang District Hospital had fulfilled the criteria as building that applied Green Hospital concept as the assessment from GBCI and had fulfilled minimum standard rating fulfillment as much as 20 points for the Silver rate. Gold rank can be achieved if it has met 25 points and Platinum rank with a minimum achievement of 31 points.